2010
DOI: 10.1309/ajcpxy17sulqkswk
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Findings in Novel Influenza A (H1N1) Virus (“Swine Flu”) Infection

Abstract: Although novel influenza A (H1N1) virus infection has assumed pandemic proportions, there are few reports of the pathologic findings. Herein we describe the pathologic findings of novel influenza A (H1N1) infection based on findings in 2 autopsy cases. The first patient, a 36-year-old man, had flu-like symptoms; oseltamivir (Tamiflu) therapy was started 8 days after onset of symptoms, and he died on day 15 of his illness. At autopsy, the main finding was diffuse alveolar damage with extensive fresh intra-alveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 17 publications
(19 reference statements)
1
13
0
Order By: Relevance
“…Our study reviews the histopathologic features of these fatalities and how they differ in certain key respects from those reported in other states. Previously published studies addressing pH1N1 influenza histopathology have reported acute and/or organizing DAD in the majority of autopsied cases (74–100%) (11–15). In our series, only 2/12 (16.7%) decedents manifested DAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study reviews the histopathologic features of these fatalities and how they differ in certain key respects from those reported in other states. Previously published studies addressing pH1N1 influenza histopathology have reported acute and/or organizing DAD in the majority of autopsied cases (74–100%) (11–15). In our series, only 2/12 (16.7%) decedents manifested DAD.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a limited number of studies addressing the histopathologic features of pH1N1 influenza fatalities (9,(11)(12)(13)(14)(15). As with other forms of influenza, histologic manifestations are not specific.…”
mentioning
confidence: 99%
“…Nakajima et al in 2012 described four autopsy cases of influenza A/H1N1 with a histopathological pattern of acute DAD who presented with influenza virus antigen-positive type II pneumocytes, perhaps indicating a direct role of the virus-infected cells in the acute alveolar damage [ 11 ]. No specific cytophatic effect or viral inclusion has been described so far at LM in lung tissue specimens during influenza pneumonia [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported histophatological observations during influenza A/H1N1 2009 pneumonia: the major finding was diffuse alveolar damage (DAD) [ 1 4 ]. Type II pneumocytes were considered the main target of influenza A/H1N1 infection [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are already many autopsy series with patients with H1N1 that can be used for comparison, the pathological findings at autopsy are modified mainly by the presence of associated co-infections and mechanical ventilation. [32][33][34][35][36][37][38][39] In summary, we have presented the pulmonary pathology in a confirmed and well-defined series of cases of S-IOV infection associated with ARF. The pathological features, in addition to necrotizing bronchiolitis and DAD, included the presence of multinucleated cells and intra-alveolar fibrin exudates (organizing pneumonia-like lesions).…”
Section: Discussionmentioning
confidence: 99%